LEVERAGING AGRIVOLTAICS TO INCREASE FOOD, ENERGY, AND WATER ACCESS IN THE GLOBAL SOUTH: A CASE STUDY SUB-SAHARAN AFRICA (Nigerian Journal of Technology, 2024)
Today, about 760 million people, mostly in sub-Saharan Africa (SSA) and Asia, are without access to electricity; over 2.5 billion people are without access to clean cooking facilities and this is connected to around 2.5 million premature deaths yearly; and modern sustainable energy supply is to account for only 18% by 2030. Over half of the global undernourished lives in Asia (418 million) and over one-third are found in Africa (282 million); SSA Latin America and the Caribbean were noted for the highest food insecurity (66.2%). Sub-Saharan Africa faces complex and interconnected challenges of food, energy, and water (FEW), which have significant implications for the region's socio-economic development and the well-being of the people. The study aims to assess the socioeconomic advantages and potential drawbacks of agrivoltaics through the following study objectives: to x-ray and discuss agrivoltaics brief history, principle, and merits of agrivoltaics; to examine the impacts of shades created by PV panels on crop performance. Others are examining the impacts of panels and crops on microclimate conditions; and evaluation and identification of steps required for developing and deploying agrivoltaics in SSA in SSA. This study recognises agrivoltaics as a single-solution approach with multiple effects that need to be developed and deployed. This study identifies universities and other research institutions, governments, non-government organisations (NGOs), private sector entities, and international organizations as stakeholders that need to collaborate and invest in research on agrivoltaics. The research proposes embracing and customising agrivoltaics approaches in SSA, taking cues from the development trajectories observed in Europe and America.